PENGOLAHAN PRODUK DIVERSIFIKASI IKAN BAGI KELOMPOK WANITA NELAYAN MANDIRI DESA LAMUNDRE, KECAMATAN WATUBANGGA, KABUPATEN KOLAKA - Handayani, Fitrianti; Tojang, Djunarlin; Tasabaramo, Ilham Antarika; R, Mustafa; Mpia, La; Afa, Musadia; S, Ramlah; Muhsafaat, La Ode; Asni, Asni; Salam, La Ode Muhammad Aswad; Awaluddin, Andi (Universitas Mataram, 2024)
Lamundre Village is one of the villages located in Watubangga District, Kolaka Regency which has promising marine natural resource potential, both in the form of aquaculture and capture fisheries. Various types of fish catch produced by the Lamundre Village Community include skipjack fish 30 tons/year and lure fish 70 tons/year. The catch is only dried and sold raw to the market. However, this potential can still be increased to increase the income of the Lamundre Village Community and increase the diversity of fishery products from the village. The Lamundre Village Independent Fishermen's Women's Group is a partner that operates in the fish processing sector. The main problem with partners is the low level of knowledge and skills of group members in processing fishery products. Therefore, it is very necessary to provide training and assistance to partners in processing fishery products. The fish processing products carried out are making fish balls and fish floss. Fish balls and fish floss are one of the fish processing activities that can increase the added value and shelf life of fish. The aim of this community service activity is to improve the skills and knowledge of the Independent Women Fishermen Group partners in processing fish independently into a product, namely fish balls and fish floss. This community service activity will be carried out in September 2024 in Lamundre Village, Watubangga District, Kolaka Regency. The activity method is carried out at several stages including the observation stage, preparation stage, training and mentoring stage, and evaluation stage. The result of this community service activity is an increase in partners' skills and knowledge in making fish balls and fish floss. Based on the results of the interview, the partner's skill level became 85% and the knowledge level increased 100% after the training. Partners are able to make fish balls and fish floss according to the materials provided. The fish balls and fish floss produced in this training activity do not smell or fishy, ​​this is because the process of making fish balls and fish floss complies with the quality standards for making fish balls and fish floss (SNI 7690.2013). This community service activity is able to improve the skills and knowledge of partners in making fish balls and fish floss.